2015
DOI: 10.1364/ol.40.002072
|View full text |Cite
|
Sign up to set email alerts
|

Surface second harmonic generation from silicon pillar arrays with strong geometrical dependence

Abstract: We present experimental demonstration and analysis of enhanced surface second harmonic generation (SHG) from hexagonal arrays of silicon pillars. Three sets of Si pillar samples with truncated cone-shaped pillar arrays having periods of 500, 1000, and 2000 nm, and corresponding average diameters of 200, 585 and 1550 nm, respectively, are fabricated by colloidal lithography and plasma dry etching. We have observed strong dependence of SHG intensity on the pillar geometry. Pillar arrays with a 1000 nm period and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Moreover, the gradual shift of the azimuthal angle from the HRTEM measurements in Figure 4d suggested that the screw structure should be a twisted structure, rather than the reported thermodynamically stable stacking structure, 38 which is further affirmed by the polarization test. The broken symmetry along the [0001] direction from the twisted structures is believed to lead to their accumulated SHG effect with increasing layer number, rather than other effects, such as surface-enhanced SHG 47 or plasmonic-enhanced SHG. 48 Finally, the effective second-order nonlinear susceptibility of this spiral WS 2 nanosheet was roughly estimated, using a commercial BBO crystal as a reference sample.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the gradual shift of the azimuthal angle from the HRTEM measurements in Figure 4d suggested that the screw structure should be a twisted structure, rather than the reported thermodynamically stable stacking structure, 38 which is further affirmed by the polarization test. The broken symmetry along the [0001] direction from the twisted structures is believed to lead to their accumulated SHG effect with increasing layer number, rather than other effects, such as surface-enhanced SHG 47 or plasmonic-enhanced SHG. 48 Finally, the effective second-order nonlinear susceptibility of this spiral WS 2 nanosheet was roughly estimated, using a commercial BBO crystal as a reference sample.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to THG, peaks in the SHG spectrum are observed at 2ω frequencies correlated with the ω fundamental frequencies of the quasi -BICs. Because bulk Si is centrosymmetric, SHG is expected to arise from the breaking of symmetry at the NW surface and from field gradients due to resonant modes or tightly focused beams. ,, As shown in Figure B and Figure D, the field enhancements at the NW surface are apparent from the top view and cross-sectional | E ω | field profiles of the m = 0 and m = 1 quasi -BICs, respectively, and enhancement of SHG signals would thus be expected to occur as a result of enhanced fields close to the NW surface. Although enhancement of SHG from centrosymmetric nanostructures is often expected to occur as a result of enhanced fields components normal ( E ⊥ ) to the surface, contributions from tangential fields ( E ∥ ) at the surface as well as from strong field gradients ([ E ·∇] E ) in the Si NW have to be considered when under optical resonance conditions .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the inversion symmetry of the bulk silicon, only third-harmonic generation is possible in the dipole approximation, and one could not consider using bulk silicon for obtaining second-harmonic generation. By breaking this inversion symmetry, the surfaces of silicon appear as an interesting choice for obtaining SHG in nano-manufactured all-Silicon devices, where the surface-to-volume ratio increases [122]. In this chapter, I will briefly review some fundamental properties of silicon and present some applications of its surfaces in the context of second-harmonic generation.…”
Section: Silicon and Its (001) Surfacementioning
confidence: 99%
“…Therefore, the surfaces of Si appear as an crucial key for handling the silicon photonics, and in particular for the SHG on Sibased devices. Among the ways proposed in the literature for obtaining a SHG from silicon, we find nano-particles [142], micro-cavities [143], nano-pillars [122] or more recently strained silicon wave-guides [13]. In those nano-objects, the surface properties can become relatively important with respect the bulk properties, making the understanding of Si surfaces of major importance.…”
Section: The Role Of Silicon Surfaces In Novel Applicationsmentioning
confidence: 99%